EFFECTIVENESS OF STUDENT INTERACTION AND ACTIVE ENGAGEMENT IN DIGITAL LEARNING - Huda Ramadhan, Nurul; Shofhu Mukarib Chilmi, Ash; Kemala Rizki, Putri; Fikriyah Zahirah Akram, Shafa’; Suyani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
In today's digital era, the world is facing rapid technological advancement. Technology plays an important role in today's digital learning, but there are still many universities that do not fully understand and utilize the role of technology in teaching and learning activities. Therefore, this research aims to explore this issue by focusing on the use of technology to improve student interaction and engagement in digital learning. In addition, this research also aims to identify the impact of using technology in active learning. This study has several objectives, including: (1) to identify technology strategies to enhance student interaction and active engagement in distance learning; and (2) to identify and understand the positive impacts that can arise from the implementation of technology in the learning process. The method used in this research is a qualitative approach through literature review, where data is collected from various books and journals relevant to this topic. The results show that appropriate technology and learning models that are relevant to the development of the digital age have a significant impact on students' learning success. Learning models relevant to this research include: active learning, discovery learning, and mind mapping. Keywords: Digital learning, interaction, active engagement, active learning, discovery learning, mind mapping.